Exploring Combined Effect of Abiotic (Soil Moisture) and Biotic (Sclerotium rolfsii Sacc.) Stress on Collar Rot Development in Chickpea - Tarafdar, Avijit; Rani, T. Swaroopa; Chandran, U. S. Sharath; Ghosh, Raju; Chobe, Devashish R.; Sharma, Mamta (Frontiers in Plant Science, 2018)
Plants being sessile are under constant threat of multiple abiotic and biotic stresses within its natural habitat. A combined stress involving an abiotic and a biotic factor reportedly increases susceptibility of the plants to pathogens. The emerging threat, collar rot disease of chickpea (caused by Sclerotium rolfsii Sacc.) is reported to be influenced by soil moisture condition (SMC). Hence, we studied the influence of differential SMC viz. upper optimum (100%), optimum (80%), lower optimum (60%), and limiting (40%) soil moisture conditions on colonization and collar rot development over the course of infection in two chickpea cultivars, Annigeri (susceptible to collar rot) and ICCV 05530 (moderately resistant to collar rot). Disease incidence was found to be directly proportional to increase in soil moisture (R2 = 0.794). Maximum incidence was observed at 80% SMC, followed by 100 and 60% SMC. Expression of genes (qPCR analysis) associated with host cell wall binding (lectin) and degradation viz. endopolygalacturonase-2, endoglucosidase, and cellobiohydrolase during collar rot development in chickpea were relatively less at limiting soil moisture condition (40%) as compared to optimum soil moisture condition (80%). As compared to individual stress, the expression of defense response genes in chickpea seedlings were highly up-regulated in seedlings challenged with combined stress. Our qPCR results indicated that the expression of defense-related genes in chickpea during interaction with S. rolfsii at low SMC was primarily responsible for delayed disease reaction. Involvement of moisture and biotic stress-related genes in combined stress showed a tailored defense mechanism.